Topological vs. lexical determination in English particle verbs (PVs) - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Renata Geld University of Zagreb, Croatia   ABSTRACT The central aim of this work is to describe semantic determination, i.e., topological vs. lexical determination, by investigating aspects of construal (Langacker 1987) in English PVs with in and out. The paper focuses on L2 processing related to what we might call strategic thinking about linguistic meaning. More specifically, it attempts to demonstrate the following: a) how the nature of verbs affects the overall semantic determination of particle verb constructions, and b) if/how the users of English make sense of particle verbs, and how much they rely on topological/grammatical components in the process of constructing meaning. The results suggest that the nature of verbs does affect the users' strategic meaning construal - it differs in terms of their tendency towards one of the following types of semantic determination: a) topological, b) lexical, and, c) compositional.